Marine reserve establishment and on-going management costs: A case study from New Zealand. (October 2015) - Rojas-Nazar, U.A.; Cullen, R.; Gardner, J.P.A.; Bell, J.J.
Abstract: While there is considerable international research focused on the conservation outcomes of marine protected areas (MPAs) and marine reserves (MRs) there is little information on the economic cost to establish and manage these protected areas. This study estimated the MR pre-establishment and establishment costs for the Taputeranga Marine Reserve (TMR) in New Zealand (NZ) and determined the annual management costs for this reserve and four further NZ MRs. Finally, the cost to local rock lobster fishers resulting from the displaced fishing effort once the TMR had been established was estimated. This research found that the TMR pre-establishment cost was approximately NZ508, 000, and the establishment process cost was approximately NZ353, 000. The annual management costs across the five reserves ranged between NZ43, 200 and NZ112, 500 between 2008/09 and 2010/11. The annual fishers displacement cost at TMR was approximately NZ22, 000 per annum. This research showed that on a unit area basis, small MRs in NZ are just as expensive to maintain as large MRs. This study also highlighted how volunteer effort helped to considerably reduce the monetary cost of the MR pre-establishment process. This research increases our understanding of establishment and management costs, and supports future planning of MRs both within NZ and internationally. Highlights: There is little information on the cost of establishing marine reserves. We estimated the pre-establishment and establishment costs for a marine reserve. The pre-establishment cost was NZ508, 000, and the establishment cost NZ353, 000. Annual management costs ranged between NZ43, 200 and NZ112, 500. Our research supports future planning of MRs both within NZ and internationally.